Supporting document management by using RFID technology. (10th December 2007) - Bodhuin, Thierry; Preziosi, Rosa; Tortorella, Maria
A transition from traditional paper documents to digital ones is taking place, and standard ways for electronically managing documents are experimented. However, documents having legal value cannot be completely replaced by digital ones and must be kept in paper format. The authors claim that the adoption of RFID technology in an organisation helps to link, track and identify paper documents, and allows capturing additional data regarding the organisation information system and enriching the set of information produced by a traditional document management system. This paper presents an approach for building an RFID document management service.